2012
DOI: 10.5194/bg-9-5231-2012
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen isotope ratios in the shell of <i>Mytilus edulis</i>: archives of glacier meltwater in Greenland?

Abstract: Abstract. Melting of the Greenland Ice Sheet (GrIS) is accelerating and will contribute significantly to global sea level rise during the 21st century. Instrumental data on GrIS melting only cover the last few decades, and proxy data extending our knowledge into the past are vital for validating models predicting the influence of ongoing climate change. We investigated a potential meltwater proxy in Godthåbsfjord (West Greenland), where glacier meltwater causes seasonal excursions with lower oxygen isotope wat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 59 publications
1
8
1
Order By: Relevance
“…Recent shell growth was seen as a narrow band at the shell edge. This result agrees with a recent study of oxygen isotope ratios in the shell of Mytilus edulis in the Godthåbsfjord, indicating that growth checks are formed during winter growth cessation (Versteegh et al 2012).…”
Section: Age Structure and Mortalitysupporting
confidence: 92%
See 2 more Smart Citations
“…Recent shell growth was seen as a narrow band at the shell edge. This result agrees with a recent study of oxygen isotope ratios in the shell of Mytilus edulis in the Godthåbsfjord, indicating that growth checks are formed during winter growth cessation (Versteegh et al 2012).…”
Section: Age Structure and Mortalitysupporting
confidence: 92%
“…In terms of salinity, the glacier-fjord-ocean transect provides a clear gradient. A recent study reported summer minimum values as low as <10 psu in surface waters in the inner part of Godthåbsfjord during peak melt water runoff and suggested that M. edulis ceased growing at salinities <19 psu (Versteegh et al 2012). However, our data did not reveal any trends in the overall growth patterns that could be related to inhibition by the low salinity in the inner part of the fjord.…”
Section: Growth and Mortalitycontrasting
confidence: 54%
See 1 more Smart Citation
“…The presence of marine-terminating glaciers was found to explain sustained high productivity in fjords in Greenland (Meire et al, 2017). Interpretation of paleo-climatic proxies from fjords in Greenland (e.g., Versteegh et al, 2012) similarly depends on a knowledge of spatial gradients toward the open ocean. Thus, the exchange between the fjord and the open ocean and the link between this exchange and the fjord's seasonal circulation system is important for understanding physical conditions, biogeochemical cycling, and ecosystem dynamics inside fjords around Greenland.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis was performed on a Picarro Isotopic Water Analyzer, L2120-I (Picarro, Sunnyvale, USA) equipped with a PAL auto sampler (Leap Technologies, Carrboro, USA). Details of the method can be found in Versteegh et al (2012). Results are expressed in standard δ 18 O notation using the Vienna Standard Mean Ocean Water (VSMOW) standard as a reference.…”
Section: Water Stable Isotope (δ 18 O)mentioning
confidence: 99%